Temozolomide as Second or Third Line Treatment of Patients with Neuroendocrine Carcinomas - Ingrid H. Olsen; Jens B. Sørensen; Birgitte Federspiel; Andreas Kjaer; Carsten P. Hansen; Ulrich Knigge; Seppo W. Langer (The Scientific World Journal)
Background. Knowledge of the clinical efficacy in recurrent neuroendocrine carcinomas is sparse. Treatment with temozolomide alone or in combination with capecitabine and bevacizumab has recently shown promising results. Patients and Methods. Analysis of consecutive patients with neuroendocrine carcinomas (Ki-67 proliferation index >20%) and performance status 0–2 treated with temozolomide 200 mg/sqm orally days 1–5 every 28 days after at least one previous platin-containing chemotherapy regimen. Results. Twenty-eight eligible patients received a median of 3 courses. Sixteen patients were evaluable for response: Six achieved stable disease and ten progressed. The median survival for the 28 patients was 3.5 months. Survival in patients with tumors of pancreatic origin (n=7) was 7.0 months versus 2.9 months in non-pancreatic origin (n=21). Patients in PS 0-1 (n=22) had a median survival of 4.5 months versus 1.1 months in patients in PS 2 (n=6). Ki-67 index ≥50% was associated with a significantly shorter median survival than Ki-67 index <50% (2.7 months versus 10.9 months). The treatment was well tolerated. Conclusion. Temozolomide monotherapy has limited effect in treatment of recurrent neuroendocrine carcinomas. Second line treatment with temozolomide in combination with other compounds should be further investigated in patients in good performance with Ki-67 index <50%.